(untitled) (Brazilian Journal of Radiation Sciences, 2019)
LabPET GE 4 (a small animal positron emission tomograph) image acquisition is done by 1536 independents channels. Differences in the rate counting of each channel must be corrected so as not compromise image quality. Equipment user manual recommends that normalization of the detectors efficiency be made as often as possible and always whenever there are hardware or software parameters changes - included, but not limited to channels parameters adjustments, electronic cards replacements, channels activation or inactivation or software update. This work evaluates the normalization effects on the image quality parameters. PET image acquisition were performed using recommended parameters by the NEMA NU 4-2008 standards. Image was reconstructed in different ways using different normalization files. The tests performed indicated that the image quality parameters do not vary significantly with different normalization data. Therefore, a daily routine of normalizations is not justified, suggesting a periodical frequency of one month or more for this procedure.